2021
DOI: 10.21203/rs.3.rs-221344/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of alternative splicing signature in lung squamous cell carcinoma

Abstract: Increasing evidence demonstrated that alternative splicing (AS) played a vital role in tumorigenesis and clinical outcome of patient. However, systematically analysis of AS in lung squamous cell carcinoma (LUSC) is lacking and greatly necessary. Thus, this study was to systematically estimate the function of AS events served as prognostic indicators in LUSC. Among 31,345 mRNA AS events in 9,633 genes, we detected 1,996 AS in 1,409 genes which have significantly connection with overall survival (OS) of LUSC pat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is well believed that subtype-specific and progression-specific splicing aberrations would usher us into an unprecedented era of cancer studies [16]. Recently, a few studies in LUSC have done some integrative analysis about the prognostic value of AS [40,41]. However, the comprehensive evaluation of those AS events involved in splicing pattern shifts or the LNM status of LUSC is still lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well believed that subtype-specific and progression-specific splicing aberrations would usher us into an unprecedented era of cancer studies [16]. Recently, a few studies in LUSC have done some integrative analysis about the prognostic value of AS [40,41]. However, the comprehensive evaluation of those AS events involved in splicing pattern shifts or the LNM status of LUSC is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al and Li et al systematically identified the prognostic AS signature in NSCLC, the former group conducted prognostic AS models from the perspective of different sexes [48], and the latter group firstly created prognostic predictors with one type or all types of AS events in LUSC [70]. Yan et al and Liu et al also built prognostic models for seven types of AS events one by one recently [40,41]. In this aspect, our study used combined algorithms and constructed a final prognostic risk score model with a few AS events, which focused on detailed indicators rather than an overview of AS-prognosis significance.…”
Section: Discussionmentioning
confidence: 99%